X-Ray based navigation system for torsional correction - first clinical data. Issue 4 (27th April 2017) - Grünwald, Leonard; Buschbaum, Jan; Lobenhoffer, Philipp; Windolf, Markus; Schröter, Steffen
Aims and Objectives: : It is well known that treatment of femoral shaft fractures can lead into torsional malalignment. In up to 15% of these cases a torsional correction is necessary. Further there are congenital torsional abnormities causing disbalances in the knee joint. In both cases a torsional correction osteotomy can be helpful. However the results of these kind of osteotomies can defer from the planned correction-angle. There are various intraoperative tests to check the corrected angle with the planned one. But still there are a lot of unsatisfying results. It is well known that there exist navigation systems for this kind of surgery. But usually they are expensive, time consuming and need a lot of hardware. The so called X-in-One system is a truly x-ray-based navigation system. Besides the c-arm two probes and one tablet pc are needed. The objective of this study was to proof the feasibility in a clinical setting. Additionally it was meant to be a validity check. Materials and Methods: : After testing two cadaver legs in the laboratory we received the ethical approval to perform a first clinical trial. From November 2016 to June 2017 we included 5 patients who underwent torsional correction of their femur. Planning of rotational-angle was done by CT and measured with the Waidelich-method. After surgery CT and measurement was performed again to verify the success of surgery. During surgery the angle was measured with two wire technique and an angle template. To stabilize the osteotomized bone during surgery we used an external fixator. Therefore we could attach both navigation probes at each Schanz'screw (distal and proximal to the osteotomy). The surgeon was blinded to the results of the system. So the calculation was performed by the system after surgery. Therefore we took two x-ray images done during surgery, one before osteotomy and the other after the correction was stabilized. With these values we were able to calculate the validity of the new system to the CT-measurement and against the intraoperative measurement of the surgeon. Results: : In all 5 patients no adverse events, such as infection or non-union occurred. In one case the Schanz'screw with the attached probe was rotated during sugery accidentally. However the system detected this rotation correctly. There was no significant time delay by attaching and removing the probes. All intraoperative x-rays could be used as values for calculations of the X-in-One System. The results of our new system are impressive precise. No deviation more than 1° towards the CT measurement was recognized. Conclusion: : After finishing the development of this system it will be an easy to use tool for torsional corrections of each bone. It is very helpful to perform precise torsional osteotomies without apparent disadvantages during surgery performance and patients' safety. An additional benefit is that post-op CT is unnecessary. But still a lot of work has to be done to implement this system into the c-arm and get the certificate for intraoperative usage.